2016
DOI: 10.1681/asn.2015070731
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic Peptide Receptor Guanylyl Cyclase-A in Podocytes is Renoprotective but Dispensable for Physiologic Renal Function

Abstract: The cardiac natriuretic peptides (NPs), atrial NP and B-type NP, regulate fluid homeostasis and arterial BP through renal actions involving increased GFR and vascular and tubular effects. Guanylyl cyclase-A (GC-A), the transmembrane cGMP-producing receptor shared by these peptides, is expressed in different renal cell types, including podocytes, where its function is unclear. To study the effects of NPs on podocytes, we generated mice with a podocyte-specific knockout of GC-A (Podo-GC-A KO). Despite the marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 61 publications
5
37
0
1
Order By: Relevance
“…In this context, it is important that TDT treatment reduced TRPC activity both in vitro and in vivo, contributing to the prevention of glomerulosclerosis. Interestingly, we also demonstrated that TRPC-mediated calcium influx was inhibited by PKG inhibitor, consistent with the previous report that the renal dysfunction by GC-A gene ablation is attenuated by a TRPC inhibitor (Staffel et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, it is important that TDT treatment reduced TRPC activity both in vitro and in vivo, contributing to the prevention of glomerulosclerosis. Interestingly, we also demonstrated that TRPC-mediated calcium influx was inhibited by PKG inhibitor, consistent with the previous report that the renal dysfunction by GC-A gene ablation is attenuated by a TRPC inhibitor (Staffel et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Further studies would be required to make clear whether TDT shows clinical benefits additive to NEP inhibitors. Recent studies using genetically modified mice showed that podocyte-specific ablation of the NP receptor GC-A gene results in increased susceptibility to renal injury (Staffel et al, 2017), indicating that GC-A in podocytes play important roles in renal protection; however, it remains to be fully elucidated whether pharmacological activation of the NP receptor protects kidneys from chronic stress, because conventional NPs are rapidly degraded by NEP. Here, using TDT, we successfully demonstrated that chronic activation of GC-A by long-acting NPs prevented renal dysfunction accompanied by protection of podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Lines of evidence support that the pGC-A/cGMP signaling pathway plays a critical role maintaining renal physiological integrity and protecting the kidney from injury [40][41][42][43][44] . One of the key pathophysiological pathways targeted by pGC-A is apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ПНП, сериновая протеаза, превращающая проПНП в активный пептид, НЭП и ГЦА-рецепторы экспрессированы в клетках нефрона, особенно в проксимальных канальцах и собирательных трубках, локализованных в мозговом веществе почек. Высокая плотность ГЦА-рецепторов обнаружена в подоцитах клубочков и гломерулярных мезангиаль-ных клетках [25][26][27]. Циркулирующие НУП и образу-ющийся локально ПНП прямо ингибируют реабсорб-цию натрия в проксимальном и дистальном сегментах нефрона, ослабляя стимулирующий эффект НА и АТ II [28], и способствуют увеличению СКФ, вызывая дилатацию прегломерулярных и сужение постгломе-рулярных артериол клубочков [29].…”
Section: Discussionunclassified